2019
DOI: 10.1021/jacs.9b09157
|View full text |Cite
|
Sign up to set email alerts
|

Arm Growth and Facet Modulation in Perovskite Nanocrystals

Abstract: Highly emissive isotropic CsPbX3 (X = Cl, Br, and I) perovskite nanocrystals are typically observed in a six-faceted cube shape. When a unique approach is adopted and the reaction medium is enriched with halides, arm growth on all six facets was carried out and reported. Analysis suggested that these armed nanostructures were obtained from intermediate polyhedron shaped structures having 26 facets, and these were formed under halide-deficient conditions. Surface energy calculations further supported the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(168 citation statements)
references
References 46 publications
8
159
1
Order By: Relevance
“…[1b,4a, 6b,13] The crystal phase of the obtained nanocubes and hexapods were characterized by powder X-Ray diffraction (Figure S3), and the pattern resembles the orthorhombic phase according to the literature. [14] Thes calability of this approach is demonstrated by increasing the volume of the two precursors in the reaction medium by 25 times to obtain 160 mL of CsPbBr 3 NC colloidal solution in as ingle run, with the same concentration as in small-scale synthesis.T he CsPbBr 3 NCs thus obtained exhibit the optical features and morphology (nanocubes of ~9.3 nm) similar to those prepared in small-scale synthesis (see Figure S2). This makes the hot-plate approach promising for obtaining perovskite NCs for industrial-scale device applications in the future.…”
Section: Resultsmentioning
confidence: 99%
“…[1b,4a, 6b,13] The crystal phase of the obtained nanocubes and hexapods were characterized by powder X-Ray diffraction (Figure S3), and the pattern resembles the orthorhombic phase according to the literature. [14] Thes calability of this approach is demonstrated by increasing the volume of the two precursors in the reaction medium by 25 times to obtain 160 mL of CsPbBr 3 NC colloidal solution in as ingle run, with the same concentration as in small-scale synthesis.T he CsPbBr 3 NCs thus obtained exhibit the optical features and morphology (nanocubes of ~9.3 nm) similar to those prepared in small-scale synthesis (see Figure S2). This makes the hot-plate approach promising for obtaining perovskite NCs for industrial-scale device applications in the future.…”
Section: Resultsmentioning
confidence: 99%
“…However, except the intrinsic parameters such as chemical composition (e.g., different organic derivatives and/or halides), size, and band gap of PQDs that immediately determine the performance of such devices, exterior factors including the working conditions, fabrication technology, and especially photostability of individual PQD are also strictly related. For example, PQDs are very sensitive to oxygen and humidity, organic molecule substituted PQDs are prone to dissociation or phase change upon UV irradiation, while inorganic PQDs may self‐assemble into nanowires when induced by visible light, ultrasonication or anion exchange; Two‐dimensional perovskite nanosheets can self‐assemble into ordered ruddlesden‐popper phase when naturally aged, and highly emissive isotropic CsPbX 3 nanocrystals are typically obtained in a six‐faceted cubic shape when the reaction medium is enriched with halides . These behaviors are closely related with the surface chemistry of individual PQD and clear understanding of which holds the key to unveiling myriads of chemical and physical puzzles encountered towards the practical applications of perovskites.…”
Section: Methodsmentioning
confidence: 99%
“…34 Furthermore, Chen and co-workers have reported the solvothermal synthesis of CsPbBr 3 dodecapods, whilst Peng et al recently reported halide-controlled facet growth leading to dimension-tunable multipod nanostructures for perovskite NCs. 35,36 However, both the arm length and arm-core ratio obtained using this method are low, with 10 nm arms on 50 nm cores yielding an arm : core ratio of 0.2. To facilitate further applications, for example in self-assembled mesostructures, it is imperative to exert control over arm growth, and to achieve extended arm growth of branched colloidal NCs.…”
Section: Introductionmentioning
confidence: 97%